Glyfosatförbudets förväntade effekter på växtodlingsstrategin : en företagsekonomisk fallstudie om beslut och resursutnyttjande - Hylander, Lucas; Johansson, Erik; Lönnqvist, Herman (SLU/Dept. of Economics, 2018)
According to LRF Konsult, who carried out a survey named Lantbruksbarometern 2016, a large proportion of the participating farmers stated that their profitability is low or indeed very low. The Swedish agricultural sector has gone through substantial structural changes, which has led to an increasing competition. Along with the European Union´s proposition to ban the active substance glyphosate, debate among several stakeholders have aroused. A glyphosate ban could enhance the impression of a low profitability among farmers. Furthermore, a glyphosate ban would likely affect the current strategy of farmers’ cropping systems. To handle the effects of a glyphosate ban a strategy could be of use. To examine what strategy is the most sufficient, it is of great deal to make decisions. From here, a strategy may be formed along with defining long term goals.